Boundary Layer Mixture Model for a Microbubble Drag Reduction Technique. (14th July 2011) - Tsai, Jing-Fa; Chen, Chi-Chuan
Abstract : The boundary mixture model is derived to predict the performance of the microbubble drag reduction technique for a flat plate. The flat plate with a porous material microbubble injecting system and resistance-measuring system are set up to measure the frictional resistance of the flat plate without and with injected microbubbles. The tests are conducted in a water tunnel and a towing tank. The test results show that the boundary mixture model predicts the drag reduction well for the flat plate when testing with injected microbubbles in the water tunnel. However, the boundary mixture model overestimates the drag reduction effect for the flat plate tested in the towing tank. The possible mechanism for the overestimation of drag reduction effect in the towing tank may be due to the different behaviors of microbubbles in the velocity gradient of boundary layer.